2011
DOI: 10.1002/hep.24500
|View full text |Cite
|
Sign up to set email alerts
|

Fighting against viral hepatitis: Lessons from Taiwan

Abstract: Viral hepatitis and its sequelae are important health problems worldwide, including Taiwan. For the last 40 years, Taiwan's scientists and health care providers have worked hard to control these sequelae, and the results have been excellent. The author, Ding-Shinn Chen, had a key role in planning and establishing the control program in Taiwan, and participated in the endeavors from the very beginning. In this perspective, he describes how he became interested in research as a medical student, his encounters wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 95 publications
0
56
0
Order By: Relevance
“…Patients with chronic HBV infection have 25-40% estimated lifetime risk of developing adverse outcomes such as cirrhosis and hepatocellular carcinoma (HCC). 1,2 In the meantime, there is an annual incidence of 1-2% for hepatitis B surface antigen (HBsAg) clearance in hepatitis B e antigen (HBeAg)-negative patients, implicating a sustained immune control of HBV infection with favourable outcomes. [3][4][5] In clinical practice, two quantifiable viral factors, including HBV DNA and HBsAg levels, have been used used to evaluate viral activity.…”
Section: Hepatitis B Virus (Hbv) Infection Is a Global Healthmentioning
confidence: 99%
“…Patients with chronic HBV infection have 25-40% estimated lifetime risk of developing adverse outcomes such as cirrhosis and hepatocellular carcinoma (HCC). 1,2 In the meantime, there is an annual incidence of 1-2% for hepatitis B surface antigen (HBsAg) clearance in hepatitis B e antigen (HBeAg)-negative patients, implicating a sustained immune control of HBV infection with favourable outcomes. [3][4][5] In clinical practice, two quantifiable viral factors, including HBV DNA and HBsAg levels, have been used used to evaluate viral activity.…”
Section: Hepatitis B Virus (Hbv) Infection Is a Global Healthmentioning
confidence: 99%
“…They are the major causes of chronic hepatitis, which often leads to fibrosis progression, cirrhosis, and hepatocellular carcinoma (HCC) and, thus, poses a great threat to public health (1). Several potent antiviral agents with a minimal drug resistance profile are shown to persistently suppress HBV replication in patients with chronic hepatitis B (CHB), leading to a reduction or even a reversal of hepatic fibrosis in the treated patients (2).…”
mentioning
confidence: 99%
“…Chronic HBV infection is the leading cause of cirrhosis and hepatocellular carcinoma around the world (41). A study on the candidates for marriage in Iran showed a low prevalence of HBV.…”
Section: Discussionmentioning
confidence: 99%